7 - The Social Act of Exchange in Power Relations: The study of the Phenomenon of Nichekeleko at the Weighbridges in Zambia. - Chidongo Phiri (African Sociological Review, 2017)
This article examines the widely practiced phenomenon of Nichekeleko at the Weighbridges (WBs) in Zambia. The commonly held understanding of Nichekeleko by the Zambian people is that, it is corruption; ranging from bribery, theft, embezzlement, gratification to favouritism. Sociologically, the phenomenon was conceived as a social act of exchange within the context of power relations by the actors who engage in it. Foucault’s notion of power relations and Bourdieu’s concepts of “practice” and “fields’’ provided the theoretical framework for the study. Power was considered as a system, and a network of relations, encompassing the whole society than a relation between the oppressed and the oppressor. Methodologically, this study was based on mixed method research; the large part of it involving participant- observation, interviews and administering of questionnaires The argument in this paper is that failure to analyse corruption from a linguistic and philosophical perspective implied in ‘Nichekeleko’ reduces the practice to mere violation of the law or moral rules. A much closer look at corruption from a language vantage point p us with essential dimensions of the practice, why, and how it has persisted in Zambia